Manual for reporting 2021 antimicrobial resistance data within the framework of Directive 2003/99/EC and Decision 2020/1729/EU. Issue 5 (19th May 2021) - (EFSA), European Food Safety Authority; Amore, Giusi; Beloeil, Pierre‐Alexandre; Fierro, Raquel Garcia; Guerra, Beatriz; Alexandra Papanikolaou; Rizzi, Valentina; Stoicescu, Anca‐Violeta
Abstract : This manual provides guidance for reporting antimicrobial resistance under the framework of Directive 2003/99/EC and Commission ImplementingDecision 2020/1729/EU in food‐producing animalsand foodstuffs derived thereof. The objective is to harmonise and streamline the reporting made by the Member States to ensure that the antimicrobial resistance data collected are relevant and easy to analyse at the European Union level. Detailed guidelines are provided for the reporting of data and text forms. This guidance typically applies to Salmonella spp., indicator commensal Escherichia coli, Campylobacter coli and Campylobacter jejuni, and the animal populations and food categories to be reported on. Guidance is also provided on indicator Enterococcus and meticillin‐resistant Staphylococcus aureus . The manual notably includes specific guidance for reporting mandatory data on Salmonella spp. and commensal indicator E. coli producers of ESBLs/AmpCs/carbapenemases obtained from the harmonised routine monitoring, and ESBL‐/AmpC‐/carbapenemase‐producing E. coli derived from specific monitoring.This manual is specifically aimed at guiding the reporting of information deriving from the year 2021.